2017
DOI: 10.1208/s12248-017-0053-0
|View full text |Cite
|
Sign up to set email alerts
|

Phloretin Prevents High-Fat Diet-Induced Obesity and Improves Metabolic Homeostasis

Abstract: Reactive oxygen species generated as a by-product in metabolism play a central role in the development of obesity and obesity-related metabolic complications. The objective of the current study is to explore the possibility to block obesity and improve metabolic homeostasis via phloretin, a natural antioxidant product from apple tree leaves and Manchurian apricot. Both preventive and therapeutic activities of phloretin were assessed using a high-fat diet-induced obesity mouse model. Phloretin was injected intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 52 publications
4
59
0
Order By: Relevance
“…We have previously shown that blockade of HFD-induced inflammation is a successful strategy to repress weight gain and improve obesity-associated complications (2730). In this study, we examined the protective activity of BITC and S -carvone against HFD-induced obesity, fatty liver, and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that blockade of HFD-induced inflammation is a successful strategy to repress weight gain and improve obesity-associated complications (2730). In this study, we examined the protective activity of BITC and S -carvone against HFD-induced obesity, fatty liver, and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance increases gluconeogenesis and decreases blood glucose absorption, leading to glucose intolerance. Many studies have shown that antioxidants are effective in blocking inflammation, increasing insulin sensitivity and improving glucose homeostasis (9, 30, 31). Consistent with these studies, our results show that BITC and S -carvone treatment alleviated insulin resistance and improved glucose intolerance in HFD-fed mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that phloretin may facilitate adipogenesis in preadipocytes and promote lipolysis in mature adipocytes. Several in vivo studies have shown that the administration of phloretin improves hyperglycemia, insulin resistance [ 20 , 21 ], and obesity [ 20 ] in diabetic rodent models. However, no studies have investigated the effects of phloretin on the commitment of multipotent marrow stromal cells (MSCs) to the adipocytes and its underlying mechanisms, including the contribution of glucose uptake inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Phloridzin has been reported can improve obesity, insulin resistance and liver lipid degeneration [21]. Phloretin can prevent HFD-induced obesity and improve metabolic homeostasis [22]. Based on the hypoglycemic and hypolipidemic potential of related species in animal models, and diversi ed in vitro and in vivo pharmacological properties of EMT, the current experiment was designed to evaluate the anti-MS effect of M. toringoides leaves against HFruD-induced mice.…”
Section: Discussionmentioning
confidence: 99%